THE RELATIONSHIP BETWEEN SUCCESS AND HARD WORK - Kenjayeva Barchinoy (TADQIQOTLAR, 2026)
Annotation: This article explores the close relationship between success and hard work. It explains how consistent effort, determination, and perseverance play a crucial role in achieving personal and professional goals. The article also discusses why talent alone is not enough without hard work. Through examples and explanations, it shows that success is often the result of continuous effort rather than luck.